A power and energy procedure in operating photovoltaic systems to quantify the losses according to the causes. (August 2015) - Spertino, F.; Ciocia, A.; Di Leo, P.; Tommasini, R.; Berardone, I.; Corrado, M.; Infuso, A.; Paggi, M.
Highlights: A power and energy procedure is the key to determine the loss causes. The assessment of energy production relies on close and calibrated irradiance sensor. The main loss source in a large PV system is the I – V mismatch in the PV modules. Electroluminescence is the proper test to find the causes of module underperformance. Abstract: Recently, after high feed-in tariffs in Italy, retroactive cuts in the energy payments have generated economic concern about several grid-connected photovoltaic (PV) systems with poor performance. In this paper the proposed procedure suggests some rules for determining the sources of losses and thus minimizing poor performance in the energy production. The on-site field inspection, the identification of the irradiance sensors, as close as possible the PV system, and the assessment of energy production are three preliminary steps which do not require experimental tests. The fourth step is to test the arrays of PV modules on-site. The fifth step is to test only the PV strings or single modules belonging to arrays with poor performance (e.g. mismatch of current–voltage curves). The sixth step is to use the thermo-graphic camera and the electroluminescence at the PV-module level. The seventh step is to monitor the DC racks of each inverter or the individual inverter, if equipped with only one Maximum Power Point Tracker (MPPT). Experimental results on real PV systems show the effectiveness of this procedure.